2012
DOI: 10.1155/2012/757501
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Pacing in Patients with Recurrence of Symptoms and Relapse of Left Ventricular Obstruction at Midcavity Level after Alcohol Septal Ablation

Abstract: Treatment of symptom recurrence after initially successful alcohol septal ablation (ASA) in hypertrophic obstructive cardiomyopathy (HOCM) when accompanied by relapse of intracavitary left ventricular pressure gradient (LVG) is guided by the underlying mechanism. We describe our experience with permanent pacing in three patients with relapse of both LVG and symptoms 7 to 12 months after successful ASA. Even though pressure gradient recurrence was observed at midventricular level, we were able to achieve sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…The recurrence of the pressure gradient after ASA was described in about 10% of cases in the first two years after the procedure. This complication may be explained by an incomplete scar formation, an irregular form of the scar with recovery of the periinfarct tissue-often hibernating myocardium, patchy instead of dense fibrosis, a non-proper location of the scar, an incomplete interventricular septum remodeling or a midventricular migration of the obstruction [19]. In our patient, it is possible for the scarring to have migrated in the direction of the AV node, and also for a part of the hibernating myocardium near the infarction zone to have recovered instead of developing necrosis with subsequent fibrosis and scar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recurrence of the pressure gradient after ASA was described in about 10% of cases in the first two years after the procedure. This complication may be explained by an incomplete scar formation, an irregular form of the scar with recovery of the periinfarct tissue-often hibernating myocardium, patchy instead of dense fibrosis, a non-proper location of the scar, an incomplete interventricular septum remodeling or a midventricular migration of the obstruction [19]. In our patient, it is possible for the scarring to have migrated in the direction of the AV node, and also for a part of the hibernating myocardium near the infarction zone to have recovered instead of developing necrosis with subsequent fibrosis and scar.…”
Section: Discussionmentioning
confidence: 99%
“…Implantation of a dual chamber pacemaker programmed with a short AV delay, combined with the maximal tolerated betablocker therapy solved the problem in the acute phase. Right ventricular apical pacing with a short AV delay is known as a good method to reduce the LVOT pressure gradient by inducing interventricular septum contraction dyssynchrony [1], but for some reasons, the studies show that it is less efficient alone, compared with the other two septal reduction therapies [1,19]. On the other hand, many authors recommend the use of the dual chamber pacemaker when one of these techniques fails, instead of repeating the procedure [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13) Velchev et al reported the effectiveness of permanent pacing in patients with LV mid-cavity obstruction after alcohol septal ablation for LV outflow tract obstruction. 14) The mechanism of LV mid-cavity obstruction improvement in the absence of subaortic obstruction by SAM may be associated with the dyssynchronous contraction of the septum and posterior wall caused by pacing of the RV apex. 15) Because pacing is relatively noninvasive compared to surgical therapy, permanent pacing is a good option, especially for the elderly patients with LV mid-cavity obstruction and apical aneurysm.…”
Section: Discussionmentioning
confidence: 99%